The interaction of T4 endonuclease V E23Q mutant with thymine dimer- and tetrahydrofuran-containing DNA. - Latham, K A (1995)
The interaction between endonuclease V, the cyclobutane pyrimidine dimer-specific N-glycosylase/abasic lyase from bacteriophage T4, and DNA was investigated by DNase I footprinting methods. The catalytically inactive mutant E23Q was found to interact with a smaller region of DNA at the abasic site analog, tetrahydrofuran, than at a thymine dimer site. Like the wild-type enzyme, the mutant contacted the DNA substrates primarily on the strand opposite the damage. The various complexes examined by footprinting techniques represent distinct points along the catalytic pathway of endonuclease V: before catalysis at a dimer, after N-glycosylase action but before abasic lyase action, and before catalysis at an abasic site. The differences between the footprints of the mutant and wild-type enzymes on both DNA substrates likely represent subtly different conformations within these complexes.